A hipótese de incidência do ICMS e a evolução dos conceitos tradicionais de mercadoria e serviço de comunicação - Miguel, Luciano Garcia (2016)
This paper presents a critical analysis of the taxation model structured in Brazil to tax the transactions with goods and services, compared to the model used by most countries which adopt VAT for this purpose. The main flaws of the model adopted and the consequences of this decision are pointed out, especially with regard to the complexity of the system and economic inefficiency. For determination of the ICMS tax base are abandoned traditional concepts elaborated by the doctrine, to seek, in the business activities whose aim is the production and marketing of goods and services, the necessary elements for the definition